PEMANFAATAN SAMPAH BERKELANJUTAN DI DESA KEBONAGUNG DENGAN SISTEM BANK SAMPAH - Valdivian Aprilisianto; Putri Uminatul Awalliyah; Putri Milana; Dwiyan Nur Santosa; Aflih Maulana; Kheysa Valendria; Agustina Mawarni; Haifa Shani Habibatun Nasywa; Hari Setiawan; Siti Laeli Nuzul Liana; Kaila Shafa' Nuha Saffanah; Nur Imamul Muttaqien; Ahmad Asadul Ma'arif; Laely Nur Wahidah; Hidayatus Sibyan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The management of waste that is not optimal has become one of the environmental issues that continues to escalate. One solution that can be applied is to revitalize waste banks with the 3R concept (Reduce, Reuse, Recycle). This concept aims to reduce waste production, make use of items that can still be used, and recycle waste to have economic value. This article discusses strategies for revitalizing waste banks through increasing public awareness, collaboration with various parties, innovation in management systems, and the utilization of digital technology. The results of the study show that with regulatory support, attractive incentives, and active community participation, waste banks can play a more effective role in reducing environmental impacts while also creating economic opportunities. Thus, the implementation of the 3R concept in waste bank management becomes a strategic step towards realizing a cleaner and more sustainable environment.